PENGUATAN KESADARAN APARAT PENEGAK HUKUM: REPOSISI KEDUDUKAN KORBAN BERBASIS VICTIM CENTERED APPROACH DALAM SISTEM BERADILAN PIDANA - Triantono, Triantono; Setiani, Natasya Okta (Badan Pembinaan Hukum Nasional, 2026)
The criminal justice system currently still formally and procedurally has a dominant paradigm of punishing perpetrators of criminal acts. This condition places crime victims, as the most disadvantaged subjects, in marginalized spaces that receive minimal attention. One important factor influencing this condition is the lack of consciousness among law enforcement officials in understanding and internalizing the experiences of victims as part of the criminal justice process. This article aims to analyze the strengthening of law enforcement officials' consciousness from a victim perspective and its implications for victim protection in the criminal justice system. The research uses a normative juridical method through a legislative and conceptual approach, supported by relevant theories. The results of the discussion and analysis show that the consciousness of law enforcement officials from a victim-centered perspective is important and urgent to implement in order to create a criminal justice system that is responsive, provides protection for victims, and is substantively fair. Strengthening victim centered consciousness needs to be done by increasing the individual and institutional capacity of law enforcement officials through a victim centered justice approach in all stages of criminal justice.